2016
DOI: 10.15547/tjs.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 expression and oxidative stress - related markers in gastric mucosa in skin burns and protection with melatonin

Abstract: Melatonin, a major hormone of pineal gland, was recently show to attenuate acute gastric lesions induced by strong irritants because of the scavenging of free radicals. The effect of melatonin on burninduced gastric mucosal injury due to the skin burn is unclear. PURPOSE: This study investigated heme oxygenase-1 and markers linked with oxidative stress in gastric mucosa and the effect of melatonin in burn rat model. METHODS: Melatonin was applied immediately and 12 hours after 30% of total body surface area bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…In addition, melatonin reduces the membrane cytotoxic activity of TNF-α [ 52 ] and overproduction of NO/iNOS/ONOO- as well as diminishes their deleterious effects on mitochondria [ 53 ]. Our data support these claims [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, melatonin reduces the membrane cytotoxic activity of TNF-α [ 52 ] and overproduction of NO/iNOS/ONOO- as well as diminishes their deleterious effects on mitochondria [ 53 ]. Our data support these claims [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Data suggested that TNF-α induced apoptosis of enterochromaffin-like cells by activating NF kappa B and generating NO [ 37 , 38 ]. In addition, immunohistochemically, we found increased iNOS expression in the epithelial cell cytoplasm in burned rats [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS is a key enzyme of "classically activated" or "killer" macrophages (M1) and contributes to NO synthesis from L-arginin (24). In support of these results in a previous study, we found increased expression of iNOS (25). Upregulated NO/iNOS production and its interaction with superoxide radicals leads to production of highly toxic peroxynitrite radical.…”
Section: Discussionsupporting
confidence: 90%
“…The possible mechanism is via overexpression of HO-1. The upregulated HO-1could suppressed NF-κB signaling pathway and pro-inflammatory cytokines induced iNOS expression (Hristova et al 2016;Yang et al 2017). Previous studies reported that H 2 S has enhanced the activity of endothelial nitric oxide synthase (eNOS) by facilitating phosphorylation of its active site and dephosphorylation of the inhibitory site to increase the production of anti-inflammatory NO.…”
Section: Immunohistochemical Assessment Of Inosmentioning
confidence: 99%